2018
DOI: 10.1021/acs.cgd.8b00031
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Photolysis of Nitrosobenzene cis-Dimer Monitored In Situ by Single Crystal Photocrystallography

Abstract: A single crystal of the cis-dimer of nitrosobenzene was directly observed by photocrystallography to transition to a pair of monomers and reversibly redimerize. The remarkable displacement of the nitrogen atoms within the crystalmoving a total distance of 2.97(5) Å for the two atomssuggests that the breadth of solid-state photochemical reaction systems susceptible to X-ray diffraction studies need not be limited to those with very small atomic displacements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…This allows examination of relatively shorterlived species, which would otherwise relax back to the ground state. Since these two methods do not require any specific and advanced experimental setups, they have been used extensively to study structural dynamics of a variety of systems, with particular emphasis on photo-switchable materials undergoing for example photoisomerization or reversible photolysis [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Experimental Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows examination of relatively shorterlived species, which would otherwise relax back to the ground state. Since these two methods do not require any specific and advanced experimental setups, they have been used extensively to study structural dynamics of a variety of systems, with particular emphasis on photo-switchable materials undergoing for example photoisomerization or reversible photolysis [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Experimental Approachesmentioning
confidence: 99%
“…Nonetheless, despite recent advances and promising perspectives, a lot still needs to be conducted and resolved in order to fully monitor fast processes in various systems of interest (including small-molecule crystals of photoswitchable coordination complexes [31,32,45,46,170,171] or purely organic compounds [41,172,173]), and literally "watch chemistry happen".…”
Section: Summary and Prospectsmentioning
confidence: 99%
“…The azodioxy bond can be reversibly cleaved by UV light under cryogenic conditions, while redimerization or repolymerization is induced thermally. , In case of p -bromonitrosobenzene, the dimerization consists of a chemical transformation coupled to a slower phase transition . In general, the reaction heavily depends on the orientation and distance between the reacting nitroso groups, which can reach up to almost 3 Å in case of nitrosobenzene …”
Section: Introductionmentioning
confidence: 99%
“…14 In general, the reaction heavily depends on the orientation and distance between the reacting nitroso groups, 15 which can reach up to almost 3 Å in case of nitrosobenzene. 16 Azodioxides can exist in a Z or E configuration, the former being more common in solution and the latter more common in the solid state. 11 An equilibrium between the monomeric Z and E species is usually established in solution (Scheme 1, red).…”
Section: Introductionmentioning
confidence: 99%
“…29a In 1970, the first crystal structure of a cis-azodioxy dimer of an aromatic C-nitroso compound was reported when Dieterich et al, identified cis-azodioxybenzene in the solid state. 30 However, since this first report there have only been a limited number of reports of crystal structures of cis-azodioxy dimers for other aromatic C-nitroso compounds, these include; 2-methyoxynitrosobenzene, 31 nitrosotoluene, 32 and pentafluoronitrosobenzene, 33 in addition to N-heterocycles; 2-nitrosopyridine 34 and 2-nitrosoquinozaline. 35 Whilst dimers are more commonly found in the solid state, monomers can be favoured when there are resonance electron-donating groups (e.g.…”
Section: Introductionmentioning
confidence: 99%